Genomic analysis reveals the interplay between ABA-GA in determining fresh seed dormancy in groundnut - Mohinuddin, Khaja D.; Gangurde, Sunil S.; Khan, Hasan; Bomireddy, Deekshitha; Sharma, Vinay; Shah, Priya; Sagar, Nikhil U.; Dube, Namita; Senthil, Ramachandran; Tembhurne, B.V.; Nayak, V. Hanumanth; Peerzada, Ovais Hamid; et al. (Elsevier, 2025)
Groundnut is an important oilseed crop; however, its productivity and seed quality are frequently reduced due to lack of fresh seed dormancy (FSD). To address this challenge, a mini-core collection of 184 accessions was phenotyped to identify potential donors in each agronomic type. In addition, whole genome re-sequencing and multi-season phenotypic evaluations were analyzed to identify stable marker-trait associations (MTAs) linked to FSD. Phenotypic analysis revealed substantial variability in dormancy durations, with days to 50 % germination (DFG) ranging from 1 to 30 days. Multi-locus genome-wide association study (ML-GWAS) identified 27 MTAs in individual seasons and 12 MTAs in pooled seasons data, respectively. Key candidate genes identified included Cytochrome P450 superfamily proteins, protein kinase superfamily proteins, and MYB transcription factors involved in the Abscisic acid (ABA) pathway, as well as F-box interaction domain proteins, ATP-binding ABC transporters, associated with the Gibberellic acid (GA) pathway. SNP-based KASP (Kompetitive Allele-Specific Polymerase chain reaction) markers were developed for 12 SNPs, of which four markers (snpAH00577, snpAH00580, snpAH00586 and snpAH00588) were found useful for the selection of FSD. The combination of favourable allele from four genes namely Ahfsd1 (Arahy.8B3CAL), Ahfsd2 (Arahy.NRZN5K), Ahfsd3 (Arahy.JJ8FJQ), and Ahfsd4 (Arahy.PI0JM6) provides stable 24–30 days of dormancy. Incorporating favourable dormant alleles into breeding programs could enable the development of high-yielding cultivars with a dormancy period of more than two weeks.